2012
DOI: 10.1523/jneurosci.0782-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gating of Thalamocortical Signals by Reticular Nucleus of Thalamus during Locomotion

Abstract: SUMMARY The thalamic reticular nucleus (RE) provides inhibition to the dorsal thalamus, and forms a crucial interface between thalamo-cortical and cortico-thalamic signals. Whereas there has been significant interest in the role of the RE in organizing thalamo-cortical signaling, information on the activity of the RE in the awake animal is scant. Here we investigated the activity of neurons within the ‘motor’ compartment of the RE in the awake, unrestrained cat during simple locomotion on a flat surface and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…The functional significance of this finding is not clear from this experiment alone but does suggest that the TRN participates in a contralateral inhibitory circuit analogous to that seen arising from layer V of the cortex (Palmer et al, 2012), and the BOLD response recorded here may be driven by cortical-thalamic projections from this very circuit. Such an interpretation is consistent with recent findings in the walking cat (Marlinski et al, 2012), in which profound TRN modulation in the somatosensory sector was observed when the contralateral hemisphere received sensory input during stance. Our data are consistent with such a mechanism in the human brain, and also evidence that this effect can be observed in the passive state.…”
Section: Correlation Analysissupporting
confidence: 93%
See 4 more Smart Citations
“…The functional significance of this finding is not clear from this experiment alone but does suggest that the TRN participates in a contralateral inhibitory circuit analogous to that seen arising from layer V of the cortex (Palmer et al, 2012), and the BOLD response recorded here may be driven by cortical-thalamic projections from this very circuit. Such an interpretation is consistent with recent findings in the walking cat (Marlinski et al, 2012), in which profound TRN modulation in the somatosensory sector was observed when the contralateral hemisphere received sensory input during stance. Our data are consistent with such a mechanism in the human brain, and also evidence that this effect can be observed in the passive state.…”
Section: Correlation Analysissupporting
confidence: 93%
“…Because the resolution limits of our stimulus, the foveal visual field of both the TRN and LGN were not likely mapped with any specificity. This did not produce any obvious omissions in the output of our analysis, as the full extent of the fovea in each LGN was mapped in all participants (Schneider et al, 2004), it is possible that a more accurate retinotopic map of the TRN would be produced with a higher-resolution stimulus, as the visual TRN is known to have receptive fields with spatial acuity Ͻ1°in nonhuman primates (McAlonan et al, 2006). We were also limited in this respect with our ability to perform eccentricity mapping due to our stimulus resolution: future studies may want to supplement these findings with them.…”
Section: Retinotopymentioning
confidence: 99%
See 3 more Smart Citations